Application of Simple Technology in Urea Fertilizer Sowing Equipment to Increase Agricultural Productivity in Ngadisono Village - Vidiawati, Vani; Syachputra, Aryans Fito; Setiarini, Tinta Afrilina; Susanti, Isika Amalia; Al-Fatih, Layung Vyndo; Pratiwi, Galuh Wanda; Anggraeni, Anugrah; Fatimah, Nissa Nurul; Atikah, Dinar Farrah; Saputra, Ilham Dwi; Falah, Fajrul Nur; Rusman, Ade; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Fertilization is one of the important stages in plant cultivation that affects growth and crop yields. However, the manual fertilization method that is still widely used by farmers in Ngadisono Village has weaknesses, such as inaccurate dosage, uneven distribution of fertilizers, and high labor needs. This activity was carried out by Real Work Lecture (RWL)) students as a form of community service with the aim of designing and making simple urea/grain fertilizer sowing tools equipped with storage containers in the form of gallons or bags, to facilitate the fertilization process. The implementation method includes observation, design, manufacturing, trials, as well as socialization and training to farmers through the local Women Farmers Group (WFG) on the pilot land. The results of the activity show that this tool can save time and effort, increase the accuracy of dosage, and improve the distribution of fertilizers in the field. Hands-on training in the garden provides the community with practical understanding and skills so that they can operate and maintain the tools independently. This innovation is expected to be an appropriate solution that can support agricultural productivity and be applied sustainably in Ngadisono Village.